2017
DOI: 10.1101/194514
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptional development of phospholipid and lipoprotein metabolism in different intestinal regions of Atlantic salmon (Salmo salar) fry

Abstract: BackgroundIt has been suggested that the high phospholipid (PL) requirement in Atlantic salmon (Salmo salar) fry is due to insufficient intestinal de-novo synthesis causing low lipoprotein (LP) production and reduced transport capacity of dietary lipids. However, there has not been performed any in-depth ontological analysis of intestinal PL and LP synthesis with development of salmon. Therefore in this paper we used RNA-seq technology to test the hypothesis that the high PL requirement in salmon fry was assoc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 22 publications
0
5
1
Order By: Relevance
“…Dietary PLs in fish are predominately digested by phospholipase A2 into 1-acyl- sn -phospholipid (lyso-PL) and FFA, which are then absorbed and re-synthesized into new PLs in enterocytes by lysophospholipid acyltransferase (LPAT). 3 , 36 Our study has found higher amounts of PC-44:12 (DHA-DHA-PC) and PE-44:12 (DHA-DHA-PE) in salmon fed a FO diet, while fish fed a VO diet had higher amounts of PC-40:9 (likely 18:3 n -3-DHA-PC) and PC-38:8 (likely 16:0-DHA-PC). The high PL-DHA in both VO- and FO-fed salmon suggests that LPAT preferentially esterifies LC-HUFA over other fatty acids.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Dietary PLs in fish are predominately digested by phospholipase A2 into 1-acyl- sn -phospholipid (lyso-PL) and FFA, which are then absorbed and re-synthesized into new PLs in enterocytes by lysophospholipid acyltransferase (LPAT). 3 , 36 Our study has found higher amounts of PC-44:12 (DHA-DHA-PC) and PE-44:12 (DHA-DHA-PE) in salmon fed a FO diet, while fish fed a VO diet had higher amounts of PC-40:9 (likely 18:3 n -3-DHA-PC) and PC-38:8 (likely 16:0-DHA-PC). The high PL-DHA in both VO- and FO-fed salmon suggests that LPAT preferentially esterifies LC-HUFA over other fatty acids.…”
Section: Discussionmentioning
confidence: 70%
“…In parallel to the increased rate of lipid remodeling in the gut of SW salmon, we observed higher steady-state expression levels of genes involved in lipid transport pathways ( Figure 4 A). These genes include agpat 4 -a and chka-b , involved in de novo synthesis of glycerophospholipid, 36 , 37 genes mtp-a , sar 1 a-b , apobb , apoa 4 a-a , and apoa 1 -a involved in lipoprotein formation, 36 and gene fabp 2 a-b involved in intracellular transport of fatty acids. 38 In the liver, no difference was observed in the expression of genes involved in phospholipid and lipoprotein formation between the livers of SW salmon and FW salmon.…”
Section: Resultsmentioning
confidence: 99%
“…The raw sequences are publicly available on European Nucleotide Archive under accession number PRJEB21981. The raw sequence data for FO samples were used in a previous study to understand the transcriptional development of phospholipid and lipoprotein metabolism in salmon fry ( 8 ) .…”
Section: Methodsmentioning
confidence: 99%
“…Most studies on dietary lipid utilisation have focused on the pyloric caeca or midgut as they are the predominant regions for lipid absorption and transport in salmon ( 3 6 ) . The hindgut could also be involved in absorption and transport of lipids, as both histological and genetical studies have suggested an existence of lipoproteins in the region ( 7 , 8 ) . The stomach is primarily responsible for mechanical and chemical digestion of feed, but may also be involved in absorption of SCFA, Na and water ( 9 ) .…”
mentioning
confidence: 99%
See 1 more Smart Citation